Ginsenoside Rb1 mitigates oxidative stress and apoptosis induced by methylglyoxal in SH-SY5Y cells via the PI3K/Akt pathway. (December 2019) - Nan, Fengwei; Sun, Guibo; Xie, Weijie; Ye, Tianyuan; Sun, Xiao; Zhou, Ping; Dong, Xi; Sun, Jiafu; Sun, Xiaobo; Zhang, Mengren
Abstract: Diabetic encephalopathy is a severe diabetic complication characterized by cognitive dysfunction and neuropsychiatric disability. Methylglyoxal (MGO), a highly reactive metabolite of hyperglycemia, serves as a major precursor of advanced glycation end products that play key roles in diabetic complications. Ginsenoside Rb1 (abbreviated as Rb1) has received extensive attention due to its potential therapeutic effects on diabetes and neurodegeneration. Therefore, this study aimed to investigate the effects of Rb1 on MGO-induced damage in SH-SY5Y cells and the related mechanism. SH-SY5Y cells were pretreated with Rb1 for 8 h and then exposed to MGO (0.5 mM) for 24 h. Cell survival was assessed by the MTT assay. Cell apoptosis was assessed using Hoechst 33342/propidium iodide (PI) staining and an Annexin-V/PI kit. The activities of oxidative stress markers were examined using commercial kits. Reactive oxygen species (ROS) staining and JC-1 staining were used to evaluate mitochondria injury. In addition, protein levels were measured by Western blot analysis. As a result, Rb1 alleviated the injury induced by MGO by increasing the activities of superoxide dismutase, catalase and total glutathione, decreasing the level of malondialdehyde, and alleviating mitochondrial damage and ROS production. Furthermore, Rb1 could enhance the Bcl-2/Bax ratio, inhibit the expression of cleaved caspase-3 and cleaved caspase-9, and enhance the levels of phosphorylated Akt. Moreover, the protective effects of Rb1 against MGO-induced apoptosis were partly abolished by LY294002, a specific inhibitor of phosphatidylinositol 3-kinase (PI3K) phosphorylation. Our results demonstrated that Rb1 ameliorated MGO-induced oxidative stress and apoptosis in SH-SY5Y cells via activating the PI3K/Akt signaling pathway. Highlights: Methylglyoxal plays a key role in diabetic encephalopathy. Ginsenoside Rb1 protected SH-SY5Y cells from methylglyoxal-induced oxidative stress and apoptosis. The effects of ginsenoside Rb1 might be through activating the PI3K/Akt signaling pathway.